The AT(1) receptor antagonist, L-158,809, prevents or ameliorates fractionated whole-brain irradiation-induced cognitive impairment - Robbins, Mike E. (2008)
PURPOSE: We hypothesized that administration of the angiotensin type 1 (AT(1)) receptor antagonist, L-158,809, to young adult male rats would prevent or ameliorate fractionated whole-brain irradiation (WBI)-induced cognitive impairment. METHODS AND MATERIALS: Groups of 80 young adult male Fischer 344 × Brown Norway (F344×BN) rats, 12–14 weeks old, received either: i] fractionated WBI; 40 Gy of γ rays in 4 weeks, 2 fractions/week, ii] sham-irradiation; iii] WBI plus L-158,809 (20 mg/L drinking water) starting 3 days prior, during and for 14, 28, or 54 weeks post-irradiation; and iv] sham-irradiation plus L-158,809 for 14, 28, or 54 weeks post-irradiation. An additional group of rats (n = 20) received L-158,809 prior to, during, and for 5 weeks post-irradiation, after which they received normal drinking water up to 28 weeks post-irradiation RESULTS: Administration of L-158,809 prior to, during, and for 28 or 54 weeks after fractionated WBI prevented or ameliorated the radiation-induced cognitive impairment observed 26 and 52 weeks post-irradiation. Moreover, giving L-158,809 prior to, during, and for only 5 weeks post-irradiation ameliorated the significant cognitive impairment observed 26 weeks post-irradiation. These radiation-induced cognitive impairments occurred without any changes in brain metabolites or gross histologic changes assessed at 28 and 54 weeks post-irradiation, respectively. CONCLUSIONS: Administering L-158,809 prior to, during, and after fractionated WBI can prevent or ameliorate the chronic, progressive, cognitive impairment observed in rats at 26 and 52 weeks post-irradiation. These findings offer the promise of improving the quality of life for brain tumor patients.